TREATMENT POLICY OF PEDIATRICIANS AGAINST ACUTE AND CHRONIC ALLERGIC PATHOLOGIES IN CHILDREN. DESLORATADINE - E.A. Vishneva (Педиатрическая фармакология, 2009)
Allergic rhinitis, bronchial asthma, chronic idiopathic nettle rash, atopic dermatitis have been characterized by a stable growth in the prevalence of the allergic pathology over the last several decades. A similar pathogenesis of allergic diseases makes it possible to regard them as different manifestations of a systemic allergic inflammation. Histamine is one of the main mediators of an allergic inflammation, therefore first-line medications (drug of choice) in the treatment of an allergic pathology, first of all, rhinitis and chronic nettle rash, are second-generation blockers of Н1-receptors. The proposed article discusses the issues connected with the use of antihistamines for children.Key words: allergic rhinitis, bronchial asthma, nettle rash, atopic dermatitis, treatment, antihistamines, children.